Micro-RNA let-7a-5p Derived From Mesenchymal Stem Cell-Derived Extracellular Vesicles Promotes the Regrowth of Neurons in Spinal-Cord-Injured Rats by Targeting the HMGA2/SMAD2 Axis - Wang, Ying; Han, Tianyu; Guo, Ruocheng; Song, Peiwen; Liu, Yunlei; Wu, Zuomeng; Ai, Jichao; Shen, Cailiang (Frontiers in Molecular Neuroscience, 2022)
Spinal cord injury (SCI) often causes neuronal and axonal damage, resulting in permanent neurological impairments. Mesenchymal stem cells (MSCs) and extracellular vesicles (EVs) are promising treatments for SCI. However, the underlying mechanisms remain unclear. Herein, we demonstrated that EVs from bone marrow-derived MSCs promoted the differentiation of neural stem cells (NSCs) into the neurons and outgrowth of neurites that are extending into astrocytic scars in SCI rats. Further study found that let-7a-5p exerted a similar biological effect as MSC-EVs in regulating the differentiation of NSCs and leading to neurological improvement in SCI rats. Moreover, these MSC-EV-induced effects were attenuated by let-7a-5p inhibitors/antagomirs. When investigating the mechanism, bioinformatics predictions combined with western blot and RT-PCR analyses showed that both MSC-EVs and let-7a-5p were able to downregulate the expression of SMAD2 by inhibiting HMGA2. In conclusion, MSC-EV-secreted let-7a-5p promoted the regrowth of neurons and improved neurological recovery in SCI rats by targeting the HMGA2/SMAD2 axis.